Beyond the Self-Legislation Model of Democracy: James Bohman's Approach to Democratic Theory. Issue 2 (March 2018) - Warren, Mark E.
James Bohman's work involves a paradigm shift in how we conceive democracy in complex, pluralized, globalized contexts comprised of multiple, overlapping constituencies that often have broad extension in space and time. He breaks with theories that view democracy as comprised of a bounded demos legislating for itself, and which conceptualize democracy as ways of organizing territorial, state-organized political entities. Elements of a progressive democratic theory that travels across borders should be built out of three ideas: (a) a nonutopianism that pays close attention to the "circumstances of politics"; (b) institutions that enable nondomination, which helps to push conflict resolution toward the democratic media of deliberation, bargaining, compromise, and voting; and (c) reflexive institutions that enable the deliberative generation, revision, and renewal of collective procedures and decisions, and which organize the creativity, intelligence, and energy of individuals.